Reprogramming the immune system: co-receptor blockade as a paradigm for harnessing tolerance mechanisms. - Waldmann, H; Adams, E; Cobbold, S (2008)
SUMMARY: The challenge of harnessing tolerance as a therapeutic modality has been greatly influenced by dogmas dictating how self-tolerance comes about. Deletional strategies popularized from the classical work of Medawar and Owen have always demanded stringent attention to eliminating all antigen-reactive cells. This was always considered a tough call for the treatment of autoimmune disease, where the number of antigens and their identity were hard to predict. The finding, some 15 years ago, that therapeutic tolerance could be elicited with non-lytic CD4 monoclonal antibodies using regulatory T cells as major operatives has opened up a new dimension in exploiting tolerance mechanisms for drug minimization in transplantation and for providing short-term treatments for long-term benefit in allergy, autoimmunity, transplantation, and other immunopathological conditions. Resolution of the mechanisms underlying tolerance induced by CD4 co-receptor blockade have provided a general paradigm for how regulatory T cells might be directed to get the upper hand in preventing disease. They have also identified an unexpected role for tissues to contribute to their own protection.